2006
DOI: 10.1182/blood-2006-05-025148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of clonal expansion of hematopoiesis in 2 patients with paroxysmal nocturnal hemoglobinuria (PNH)

Abstract: Somatic mutation of PIGA in hematopoietic stem cells causes deficiency of glycosyl phosphatidylinositol-anchored proteins in paroxysmal nocturnal hemoglobinuria (PNH) that underlies the intravascular hemolysis but does not account for expansion of the PNH clone. Immune mechanisms may mediate clonal selection but appear insufficient to account for the clonal dominance necessary for PNH to become clinically apparent. Herein, we report 2 patients with PNH whose PIGAmutant cells had a concurrent, acquired rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 24 publications
4
86
0
9
Order By: Relevance
“…The target of let-7a is HMGA2, 37 an architectural transcription factor, whose aberrant expression contributes to clonal hematopoiesis in some cases of paroxysmal nocturnal hemoglobinuria. 38 Compared to levels in normal controls, we detected a significantly higher HMGA2 mRNA level in PMF granulocytes but not in granulocytes from patients with PV and ET. Similar findings have been reported by others.…”
Section: Discussionmentioning
confidence: 66%
“…The target of let-7a is HMGA2, 37 an architectural transcription factor, whose aberrant expression contributes to clonal hematopoiesis in some cases of paroxysmal nocturnal hemoglobinuria. 38 Compared to levels in normal controls, we detected a significantly higher HMGA2 mRNA level in PMF granulocytes but not in granulocytes from patients with PV and ET. Similar findings have been reported by others.…”
Section: Discussionmentioning
confidence: 66%
“…In these studies, the virus was relatively often inserted into the HMGA2 locus, leading to removal of binding sites for let -7 miRNA and clonal outgrowth of hematopoietic cells, which brought a long -term effect including continuous independence of blood transfusion in severe thalassemia 70) . Overexpression and/or truncation of HMGA2 has also been found in patients with PNH and MDS, in which bone marrow failure rather than proliferative hematopoiesis is a common feature 26,68,72) . Bone marrow failure in these disorders is partly due to immunologic HSC injury by autoreactive cytotoxic T lymphocytes (CTLs) that produce tumor necrosis factor (TNF) -α and interferon (IFN) -γ 73 -75) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that HMGA2 mRNA expression was significantly higher in PMF patients with JAK2V617F mutation than patients without the mutation 25) . Moreover, in two patients with paroxysmal nocturnal hemoglobinuria (PNH), a chromosomal rearrangement causing a truncation of the 3´UTR of the HMGA2 gene have been also found particularly in abnormal clone without cell surface glycosyl phosphatidylinositol proteins (PNH clone), leading to the overexpression of HMGA2 in PNH clones 68) . These findings suggested the hypothesis that overexpression of HMGA2 may confer a clonal growth advantage to an abnormal progenitor cell, thus contributing to pathogenesis in MPN or other clonal hematologic disorders (Fig.…”
Section: Overexpression and Truncation Of Hmga2mentioning
confidence: 99%
“…Preferential immune attack on normal HSC that spares the PIG-A mutant HSC is the most attractive hypothesis to explain the close relationship between AA and PNH. 32,33 However, other hypotheses such as secondary mutations, 34 resistance to apoptosis 35.36 or even neutral evolution have been proposed. 37 Regardless of the mechanism, our data suggest that PIG-A mutations arise from a multipotent HSC in both PNH and AA.…”
Section: Discussionmentioning
confidence: 99%